Perovskite-Type Oxides as the Catalyst Precursors for Preparing Supported Metallic Nanocatalysts: A Review - Yang, Qilei; Liu, Guilong; Liu, Yuan (Industrial & engineering chemistry research, 2018)
Industrial and nanometallic catalysts are composed of an active component of metallic nanoparticles tailored by one or more additives and/or other metals, which should be in interaction and highly dispersed on a support. Therefore, it is a tough challenge to design and prepare such complicated catalysts. One promising way involves using perovskite-type oxides (PTOs, or written as ABO3 according to the composition) as the catalyst precursors. That is the subject of this Review, with the aim to provide inspiration for designing and developing supported metallic nanocatalysts. The contents include ABO3, partially substituted ABO3 (A1‑y A′ y BO3, AB1‑x B′ x O3, and A1‑y A′ y B1‑x B′ x O3), and PTOs supported on a support as the catalysts precursors. In PTOs, transition metal ions at A, A′, B, and B′ sites are confined in a PTO crystallite, and those ions are mixed uniformly at the atomic level, which is the basis for using PTOs as the precursors.